Financiamiento del Estado en el acceso a la Educación Superior a través del ICETEX y el Desempeño estudiantil en relación con las Pruebas Saber Pro. (2019)
The general objective of this research was the relationship between State funding and access to Higher Education from the ICETEX and the Student Performance of the Universidad de la Costa in the Prueba Saber Pro between 2013 and 2017 sample was randomized-stratified corresponding to 428 funded students and 574 non-funded students, extracted from the different institutional programs. The methodology becomes a quantitative approach, in a descriptive-explanatory approach, in a non-experimental, transectional-descriptive design and in a positivist paradigm. For the collection of information, the techniques of review and documentary analysis were used from a theoretical approach through secondary databases where the individual reports of the performances of the Critical Reading, English, Quantitative Reasoning, Citizen Competences were used. and Written Communication of the Saber Pro Tests of said period and systematized with own instruments of Excel spreadsheets, the SPSS package and Software Graph. The results obtained under the parameters of descriptive statistics, t Student and Test z, show that State-funded students (ICETEX) demonstration a better performance in the performance of Generic Competences compared to the non-funded, a relationship that is seen strengthened, albeit tightly in the differences of the average scores, excepting this in a period of the English test